Investigation of the impact online single and multiple representation scaffolding on mathematical concept mastery and mathematical problem-solving skill - Fitria, Wenny; Susilana, Rudi; Priatna, Nanang; Rusman (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2025)
Representation plays a central role in mathematical problem solving, serving as a cognitive bridge between abstract concepts and concrete understanding. However, while prior studies have examined the effects of scaffolding in mathematics learning, limited attention has been given to the comparative impact of single versus multiple online representations, particularly in relation to students’ cognitive processes such as eye movement behavior. This study addresses this gap by investigating the effectiveness of online single and multiple representation scaffolding in enhancing students’ mathematical concept mastery, problem-solving performance, and eye movement patterns during problem-solving tasks. A quasi-experimental design was employed involving 300 high school students, randomly assigned to either a multiple representation scaffolding group (n = 150) or a single representation scaffolding group (n = 150). Data were analyzed using one-way MANCOVA, ANCOVA, MANOVA, and ANOVA tests. The results revealed that students who received multiple representation scaffolding outperformed their peers in mastering mathematical concepts, solving complex problems—including advanced-level tasks—and demonstrating more efficient visual processing, indicated by shorter fixation durations and rereading times. Furthermore, these students exhibited more adaptive strategies across varying question types (basic, combination, and advanced). The findings highlight the pedagogical advantage of using multiple representation scaffolding in online mathematics instruction, suggesting that it offers more comprehensive cognitive support and promotes deeper conceptual understanding. This study contributes to the growing body of research on digital scaffolding by evidencing the cognitive and performance-related benefits of multimodal representation and underscores its potential to inform the design of technology-enhanced mathematics learning environments.